Burkitt Lymphoma: A Potentially Curable Childhood Tumour: Experience in Ile-Ife, Nigeria (1986-2014) - Durosinmi Muheez A (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2016)
Background: Burkitt lymphoma (BL) is the commonest tumour among Nigerian children. It is reported to be highly responsive to readily available cytotoxic drugs; yet, the outcome of therapy remains abysmal. Objectives: To review the epidemiology of BL in terms of risk factors, age incidence, regional distribution, disease sub-types, examine the available treatment regimens locally and internationally and report on the outcome of treatment in Nigeria under different conditions. Methods: A comprehensive literature review on the epidemiology of BL was undertaken and results of publications and clinical trials of BL were evaluated. Results: Three major sub-types of Burkitt lymphoma are recognised in the world literature; the classic endemic BL (eBL) in sub-Saharan Africa, EBV-independent sporadic BL (sBL) found in population outside the endemic areas and the HIV-related BL (HIV-BL), which is found in regions with high incidence of HIV infection. All the sub-types have common cytogenetic abnormalities: t (8, 14), t (8, 22), and t (2, 8). The COM regimen incorporating cyclophosphamide, oncovin and methotrexate (with the intrathecal cytarabine and methotrexate), was found to be very effective for eBL. Treatment outcome was dismal for the self-financed patients treated with COM regimen between 1986 and 2000 (Group A) compared to the internationally sponsored patients treated between 2000 and 2014 (Group B). While 16.8% of Group A patients had no chemotherapy, 9.8% were lost to toxic deaths and 88% defaulted; most of the patients in group B had full chemotherapy; the Event-Free Survival (EFS) rates at 12 and 24 months were 58.3% and 53.4%, respectively. Conclusions: COM regimen with intrathecal cytarabine and methotrexate is very effective for eBL.